2017
DOI: 10.3390/ijerph14121443
|View full text |Cite
|
Sign up to set email alerts
|

Factors Effecting the Total Volatile Organic Compound (TVOC) Concentrations in Slovak Households

Abstract: Thirty five Slovak households were selected for an investigation of indoor environmental quality. Measuring of indoor air physical and chemical factors and a questionnaire survey was performed during May 2017. The range of permissible operative temperature was not met in 11% of objects. Relative humidity met the legislative requirements in all monitored homes. Concentrations of total volatile organic compounds (TVOCs) were significantly higher in the apartments than in the family houses. The average TVOC level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 44 publications
2
37
2
1
Order By: Relevance
“…Before the measurements, all the air conditions, fans, other ventilators were switched off, and all windows and doors were shut during the measurement periods. Assessments were carried out in the living rooms because they are the central rooms where members of the families spend time together (Meˇciarová et al, 2017). Also, the PM 2.5 /PM 10 was determined.…”
Section: Parameter Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the measurements, all the air conditions, fans, other ventilators were switched off, and all windows and doors were shut during the measurement periods. Assessments were carried out in the living rooms because they are the central rooms where members of the families spend time together (Meˇciarová et al, 2017). Also, the PM 2.5 /PM 10 was determined.…”
Section: Parameter Measurementsmentioning
confidence: 99%
“…Several studies on indoor air quality have been published for example, Wang et al (2008); Petry et al (2014), Chen et al (2016); Shi et al (2016); Meˇciarová et al (2017); Lee et al (2018) many of the interests were on PM, TVOC, formaldehyde, O 3 , CO, CO 2 , and other aldehydes. Many of their observations were elevated levels of the parameters over the recommended standards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indoor sources may be associated with specific frequent activities carried out by dwellers, such as cooking [15,16], cleaning [17], candle burning [18], home heating [19][20][21][22], vacuuming [15], and other activities, which increase pollutants above acceptable indoor levels. A wide range of pollutants can originate via these activities including particulate matter (PM 2.5 , PM 10 ) [23], ultrafine particles (UFP) [15,24], volatile organic compounds (VOCs) [25,26], carbon dioxide [19], carbon monoxide [19,22], formaldehyde [19], polycyclic aromatic hydrocarbons [16,27], among others. For instance, cooking was found to increase PM levels by four times the background levels in a study at 14 naturally ventilated homes of Hong Kong [28].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown the link between contaminant concentration and the application of an attached garage. It can be a significant contaminant contributor to the indoor environment [3][4][5]being the source of not only carbon dioxide but also, among other contaminants like carbon monoxide, volatile organic compounds (VOC) [6], benzene and nitrogen dioxide. Nirvan et al [3] undertook studies concerning the contaminants from a garage of a house using computer simulations.…”
Section: Introductionmentioning
confidence: 99%